1D Edge Contacts to 2D Material Heterostructures - Karpiak, Bogdan (My University, 2021)
Graphene has been in the focus of research in many fields of applications due to its unique properties. In particular, the 2D nature, low charge carrier concentration and high mobility of carriers are promising properties for the use in magnetic Hall sensors. At the same time, low spin-orbit coupling and negligible hyperfine interactions make it interesting for spin-polarized electron transport. However, single graphene layer, if unprotected, is prone to defects introduced during fabrication processes and also defects due to interfaces with other insulators or contact materials. These factors would inevitably lead to decrease of graphene device performance. By encapsulating graphene in hexagonal boron nitride (h-BN), another insulating atomically flat twodimensional (2D) material with superior interface properties with graphene, one can fabricate heterostructures for robust and high-performance devices. Utilizing one-dimensional (1D) edge contacts to graphene sheet in such devices based on 2D materials would also allow to minimize contacts-induced degradation of channel properties. The graphene/h-BN heterostructures for studied devices were prepared both by exfoliation from bulk crystals and by transfer of CVD-grown materials over large area. After patterning the 2D heterostructures, 1D edge contacts were fabricated by means of electron or laser beam lithography and electron beam evaporation of metals. In these devices, proof-of-concept for batch fabrication of Hall elements on large area all-CVD h-BN/graphene/h-BN heterostructures is demonstrated. Such 1D edge contacts of ferromagnetic materials to graphene/h-BN heterostructures are also explored for spin injection into graphene in devices with novel design. The findings described in this thesis allow to advance the graphene Hall elements fabrication technology towards large-scale, industry-compatible manufacturing and lay basis for understanding and further optimization of the phenomena that drive and influence the operation of graphene spin-based devices with novel design involving 1D edge contacts.
Keywords: graphene, hexagonal boron nitride, 2D materials, van der Waals heterostructures, 1D edge contacts, Hall sensors, nonlocal spin valve, local Hall effect